Violência & gênero nas relações afetivo-sexuais entre adolescentes - Schleiniger, Cristiane dos Santos (2014)
This dissertation analyzes and discusses violence and gender relations in affective-sexual relationships among adolescents. The study has an exploratory-descriptive design, with a qualitative approach. Data were collected with the use of focus groups, and the analysis was carried out according to Critical Discourse Analysis. Eighteen adolescents from a Pescar Project Unit located in Porto Alegre participated in this study. This dissertation is composed of three empirical papers presenting the research results. The first paper analyzes the adolescents conceptions of gender roles in affective-sexual relationships, by evidencing and problematizing both hegemonic discourses that have either supported symbolic violence or rendered it invisible, and discourses that have resisted and countered such hegemony, being able to contribute to changes in gender relations. The second paper analyzes and discusses social and cultural phenomena that have been intertwined with violence in affective-sexual relationships among adolescents, establishing a bridge between the discursive practices of the adolescents participating in this research and social, historical and cultural constructions implied in this phenomenon. The third paper aims at pointing out some methodological potentialities of focus group, aiming at providing bases for the design of strategies that include group activities with adolescents, as well as public policies and inter-sector prevention, intervention and rehabilitation programs, considering the cultural gender models existing in our society. The results have evidenced that hegemonic gender discourses are present in adolescents knowledge, opinions, beliefs and attitudes, as well as in their families expectations, and the traditional gender roles provide favorable situations for either production or invisibility of violence. The challenge is to design inter-sector programs and policies for prevention, intervention and rehabilitation of violence perpetrators and victims, in order to face violence in affective-sexual relationships among adolescents both effectively and efficaciously. Education, health, assistance and justice have been involved in both the understanding and the intervention in this phenomenon, since youths need to be integrally attended, considering the peculiarities of their life conditions.